Generation of Wind Waves in Large Streams - S.S.– DSc, Eshev; I.X., Gayimnazarov; А.R. , Rakhimov; Sh. A , Latipov (International Journal of Psychosocial Rehabilitation, 2020)
There are methods for calculating the waveforms in the reservoirs, taking into account the direct flow and the reverse direction of the flow and the limited acceleration due to the coasts.